Basics of cybercrime investigation and environmental laws and protection : a learning and teaching module for criminology students and instructors - Caballero, Nicholas S. (Philippines : Wisemans Books Trading, 2022)
"This textbook was written and published to give Criminology and Information Technology students, instructors and those engaged in studying technological and environmental sciences a better understanding of how computers are used to commit crimes and how environmental pollutants affects lives. Readers of this material will learn how computers can hold evidence of crime, as well as the role and importance of electronic information that might be discovered, how to process a crime scene containing possible electronic data and how government agencies, including law enforcement, react to certain circumstances and critical issues because this provides an outline of cybercrime, providing fundamental understanding of information technologies".
Includes bibliographical references.
English text.
Keywords: Criminal investigation -- Philippines